2015
DOI: 10.1007/s00604-015-1634-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive determination of mercury(II) using glass nanopores functionalized with macrocyclic dioxotetraamines

Abstract: Glass conical nanopores functionalized with a macrocyclic dioxotetraamine derivative (C5) are shown to enable ultrasensitive determination of Hg(II). A complex is formed between Hg(II) and C5, and this converts the functionalized glass nanopore from a rectifying state to a non-rectifying state. The presence of Hg(II) in~10 pM levels or higher can be detected by velopment of a simple, portable and convenient device for the quantitation of Hg(II) with very low limits of detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…[17] Furthermore, magnetron sputtering and ion/electron beam evaporation methods with ionic metal vapor have been employed to uniformly coat al ayer of nanometer-thick metal along the inside and outside surfaces of nanopipettes. [18][19][20] Forexample, focused ion beam microscopy has shown that the ion beam evaporation method can provide am icrometer-long metal layer with at hickness of 10 nm inside a9 0nmn anopipette ( Figure 1d). [19] Them etal layer inside/outside the nanopore not only ensures the interface for faraday reactions but also offers ar eactive surface for the further modification of analytes.B yi ncorporation of Au À Sb onds,a na-fetoprotein antibody was immobilized onto agold-coated nanopipette for monitoring kinetic antigen-antibody interactions.…”
Section: The Fabrication and Characterization Of Nanopipettesmentioning
confidence: 99%
“…[17] Furthermore, magnetron sputtering and ion/electron beam evaporation methods with ionic metal vapor have been employed to uniformly coat al ayer of nanometer-thick metal along the inside and outside surfaces of nanopipettes. [18][19][20] Forexample, focused ion beam microscopy has shown that the ion beam evaporation method can provide am icrometer-long metal layer with at hickness of 10 nm inside a9 0nmn anopipette ( Figure 1d). [19] Them etal layer inside/outside the nanopore not only ensures the interface for faraday reactions but also offers ar eactive surface for the further modification of analytes.B yi ncorporation of Au À Sb onds,a na-fetoprotein antibody was immobilized onto agold-coated nanopipette for monitoring kinetic antigen-antibody interactions.…”
Section: The Fabrication and Characterization Of Nanopipettesmentioning
confidence: 99%
“…the absence of any nanoparticles, the rectification ratio has been used to measure the concentration of metal ions as they interact with the pore wall itself. 47 However these assays are limited to one analyte and longer assay times. The use of nanoparticle based systems may allow for multiplexed assays and faster reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…For inner wall surface-based charge regulation, the stimulus from the solution that caused the charge change alters the I-V curve characteristics. By designing proper surface chemistry, metal ion concentrations can be measured through the current rectification ratio, e.g., crown ethers chemistry for the specific adsorption of K + ions (Figure 4a) [90], macrocyclic dioxotetraamine derivative functionalization for Hg 2+ ion determination at a level of 10 pM (Figure 4b) [91], and polyglutamic acid for repeatable Cu 2+ ion sensing [92]. The adsorption of positively charged metal ions increases the positive charge and, therefore, changes the current rectification ratio.…”
Section: Surface Charge Measurementmentioning
confidence: 99%